Three-dimensional (3D) slope stability analysis using stability charts. Issue 5 (28th May 2021) - Chakraborty, Arunav; Goswami, Diganta
Abstract: Stability of slopes is a very serious issue in the field of geotechnical engineering. The analysis and design of failing slopes requires a thorough knowledge of the failure mechanism in order to choose the right slope stability analysis method. The two-dimensional (2D) slope stability methods are very common to the engineers because of the simplicity in their assumptions. As a result the analysis results vary greatly between the different analysis methods. The importance of three-dimensional (3D) slope stability analysis greatly increased where the geometry of the problem becomes complex which makes it very difficult to solve using 2D analysis. A lot many 2D slope stability methods were extended to 3D methods since 1970s based on limit equilibrium (LE) and finite element approaches. In this paper, slopes were analysed using 3D limit equilibrium method (LEM) using SLIDE3 software having different geometry and soil parameters and finally stability charts were prepared to calculate the FOS of the slopes. It is found that the slope stability factor can be read from the stability charts without the need for iterations.